2019
DOI: 10.1186/s12864-019-5899-3
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of bile salt biotransformation in the human gut microbiome

Abstract: Background In the biochemical milieu of human colon, bile acids act as signaling mediators between the host and its gut microbiota. Biotransformation of primary to secondary bile acids have been known to be involved in the immune regulation of human physiology. Several 16S amplicon-based studies with inflammatory bowel disease (IBD) subjects were found to have an association with the level of fecal bile acids. However, a detailed investigation of all the bile salt biotransformation genes in the gu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 81 publications
3
38
0
Order By: Relevance
“…A reduction in secondary bile acids genes in patients with CD or UC [25, 57] as well as a reduction in DCA and LCA metabolites in highly-dysbiotic patients with UC and CD, was previously described [13], supporting our current study. The key species encoding bai clusters in our metagenomes are concordant with those identified in metagenomes of a healthy population [56].…”
Section: Resultssupporting
confidence: 91%
“…A reduction in secondary bile acids genes in patients with CD or UC [25, 57] as well as a reduction in DCA and LCA metabolites in highly-dysbiotic patients with UC and CD, was previously described [13], supporting our current study. The key species encoding bai clusters in our metagenomes are concordant with those identified in metagenomes of a healthy population [56].…”
Section: Resultssupporting
confidence: 91%
“…In addition, microbes in the oral cavity, gastrointestinal tract, and pancreatic tissue differed in patients with pancreatic cancer compared with healthy controls ( 46 ). Also, Das et al ( 47 ) linked microbial metabolites to inflammatory bowel disease and Turnbaugh et al ( 48 ) revealed changes in fecal microbial structure, gene expression, and subsequent metabolic pathways due to dietary changes. Although these studies are not without limitations, they reveal promise in the utility of fecal samples to fill the need for noninvasive, inexpensive, and specific markers of dietary intake and health status ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increase the Firmicutes to Bacteroidetes ratio, which was linked to obesity; promote the enrichment of mucin-degrading Actinobacteria; decrease beneficial gut microbiota such as Bifidobacterium, Lactobacillus, and Akkermansia (Murphy et al, 2010;Islam et al, 2011;Kim et al, 2012;Lecomte et al, 2015;Taira et al, 2015;Cao et al, 2017;He et al, 2018) Mediate the conversion of bile acids into secondary bile acids; dysbiosis is associated with impaired bile acid metabolism and inflammatory bowel diseases (Duboc et al, 2013;Zou et al, 2018;Das et al, 2019) chromosomal damage to facilitate malignant transformation. Interestingly, the production of genotoxin is not restricted to only the typically pathogenic bacteria but also commensal bacteria.…”
Section: Fats Bile Acidsmentioning
confidence: 99%
“…A dysbiosis characterized by a decrease in the ratio between Faecalibacterium prausntizii and E. coli was associated with an impaired bile acid metabolism in patients with inflammatory bowel diseases (IBD), as reflected by their higher level of fecal bile acids ( Duboc et al., 2013 ). In a recent metagenomics analysis, a lower abundance of genes of bile-metabolizing Firmicutes was detected in the gut microbiota of IBD individuals, again linking microbial dysbiosis with the disease state ( Das et al., 2019 ). Of note, the interaction between bile acids and gut microbiota is bidirectional as bile acids serve as antimicrobial agents that help shape the gut microbiome structure ( Ridlon et al., 2016 ).…”
Section: The Interactions Between Diet Gut Microbiota and Colorectamentioning
confidence: 99%